Growth of organic crystals via attachment and transformation of nanoscopic precursors - Yuan Jiang (Nature Portfolio, 2017)
Multistage crystallization pathways involving nanoscopic precursors or intermediates have been proposed for various systems. Here, the authors find compelling evidence that nanoscopic species participate in the crystallization of glutamic acid monohydrate, extending this non-classical growth mechanism to organic crystals.